2021
DOI: 10.4317/medoral.24791
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characterization of gingival type of burning mouth syndrome: a cross-sectional study

Abstract: Background The aim of this study is to investigate the prevalence of localized intraoral neuropathic pain in a cluster of patients who reported the involvement of gingival site as only clinical manifestation of dysesthesia, analysing type and distribution of symptoms. Material and Methods Burning mouth syndrome (BMS) patients were enrolled in the study. Patients were screened through laboratory test and a conventional oral examination with periodontal chart. A questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…The most prevalent site of involvement is the tongue; however, it may affect the lips, palate, gingivae, buccal mucosa, or the entire oral cavity [11]. In a cross-sectional study involving 236 BMD participants, it was found that the most commonly involved site was the tongue (63.6%) followed by gingiva (61.9%) and palate (45.3%) [12]. Bilateral pain presentation is usually reported, with variation in clinical manifestation in a specified location like the tip of the tongue.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…The most prevalent site of involvement is the tongue; however, it may affect the lips, palate, gingivae, buccal mucosa, or the entire oral cavity [11]. In a cross-sectional study involving 236 BMD participants, it was found that the most commonly involved site was the tongue (63.6%) followed by gingiva (61.9%) and palate (45.3%) [12]. Bilateral pain presentation is usually reported, with variation in clinical manifestation in a specified location like the tip of the tongue.…”
Section: Clinical Presentationmentioning
confidence: 99%